Mycobacterium tuberculosis-specific CD4+ and CD8+ T cells differ in their capacity to recognize infected macrophages. - Jason D Yang; Daniel Mott; Rujapak Sutiwisesak; Yu-Jung Lu; Fiona Raso; Britni Stowell; Greg Hunter Babunovic; Jinhee Lee; Steve M Carpenter; Sing Sing Way; Sarah M Fortune; Samuel M Behar (PLoS Pathogens)
Containment of Mycobacterium tuberculosis (Mtb) infection requires T cell recognition of infected macrophages. Mtb has evolved to tolerate, evade, and subvert host immunity. Despite a vigorous and sustained CD8+ T cell response during Mtb infection, CD8+ T cells make limited contribution to protection. Here, we ask whether the ability of Mtb-specific T cells to restrict Mtb growth is related to their capacity to recognize Mtb-infected macrophages. We derived CD8+ T cell lines that recognized the Mtb immunodominant epitope TB10.44-11 and compared them to CD4+ T cell lines that recognized Ag85b240-254 or ESAT63-17. While the CD4+ T cells recognized Mtb-infected macrophages and inhibited Mtb growth in vitro, the TB10.4-specific CD8+ T cells neither recognized Mtb-infected macrophages nor restricted Mtb growth. TB10.4-specific CD8+ T cells recognized macrophages infected with Listeria monocytogenes expressing TB10.4. However, over-expression of TB10.4 in Mtb did not confer recognition by TB10.4-specific CD8+ T cells. CD8+ T cells recognized macrophages pulsed with irradiated Mtb, indicating that macrophages can efficiently cross-present the TB10.4 protein and raising the possibility that viable bacilli might suppress cross-presentation. Importantly, polyclonal CD8+ T cells specific for Mtb antigens other than TB10.4 recognized Mtb-infected macrophages in a MHC-restricted manner. As TB10.4 elicits a dominant CD8+ T cell response that poorly recognizes Mtb-infected macrophages, we propose that TB10.4 acts as a decoy antigen. Moreover, it appears that this response overshadows subdominant CD8+ T cell response that can recognize Mtb-infected macrophages. The ability of Mtb to subvert the CD8+ T cell response may explain why CD8+ T cells make a disproportionately small contribution to host defense compared to CD4+ T cells. The selection of Mtb antigens for vaccines has focused on antigens that generate immunodominant responses. We propose that establishing whether vaccine-elicited, Mtb-specific T cells recognize Mtb-infected macrophages could be a useful criterion for preclinical vaccine development.